If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11t + 9u + 5t + 4u + 3t = 0 Reorder the terms: 11t + 5t + 3t + 9u + 4u = 0 Combine like terms: 11t + 5t = 16t 16t + 3t + 9u + 4u = 0 Combine like terms: 16t + 3t = 19t 19t + 9u + 4u = 0 Combine like terms: 9u + 4u = 13u 19t + 13u = 0 Solving 19t + 13u = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-13u' to each side of the equation. 19t + 13u + -13u = 0 + -13u Combine like terms: 13u + -13u = 0 19t + 0 = 0 + -13u 19t = 0 + -13u Remove the zero: 19t = -13u Divide each side by '19'. t = -0.6842105263u Simplifying t = -0.6842105263u
| 0.06x-0.10(x-2)=-0.02(8) | | 24=4x+16 | | -44-16y+13=-34y+46+7y | | (4x-32)/4 | | 26-7=56+1 | | -7=2h+1 | | 4b+7r=90 | | 23-5v=8 | | 0.66x+6=27 | | -2/7x=1/5 | | X-2(4)=6 | | 6x/3+x+10=40 | | f(x)=2x^2-9x-5 | | 9/252 | | 6(-4)+2x=16 | | 2x=2(-4) | | 18+-8=x | | 13(y-6)=3(4y+5)-93 | | Y-2=0(x-(-4)) | | -d+7=16+3d-2 | | (4x^1+4x-4)+(x^2+4x-8)= | | 2x+4x^2-2=5x-6x^2+4 | | (4x^2+4x-24)/(4X-8) | | X^4-2X=0 | | 2y+6x=14 | | 5=x+(10+4x) | | 23.5+3s=63.8 | | 5(x+9)=77+x | | 2x+x-23+x-17=180 | | 3y-9x=-24 | | (b+9)/12=-3 | | 10x^2-x^2=9 |